DanauMas apartment complaint management system with email notification / Mohammad Habibullah Zainol … [et al.] - Zainol, Mohammad Habibullah; Abd Rahman, Mohd Shukor; Mohd Nazri, Afiq Nazran; Abu Bakar, Fatin Nur Fariha; Hasmidan, Nur Syafiqah (Faculty of Computer and Mathematical Sciences, 2021)
Danaumas Apartment is a high-density medium rise building located in Shah Alam, Selangor. This apartment is managed by Joint Body Management (JMB). DanauMas Complaint Management System with Email Notification is a project that is develop for the resident to submit the complaint and help the employee of JMB DanauMas to manage the complaints. The problems that face by the JMB DanauMas which are the complaint received by the resident are not properly recorded and well managed by the JMB DanauMas, the process taken a lot of time and difficulties to notify the complaint status. In order to help the JMB DanauMas in managing the summitted complaint and for resident to have an online complaint system, a web-based system named DanauMas Apartment Complaint Management System with Email Notification to be developed in order to minimize the current problems. From that, the objectives are to gather and analyze the requirements need for DanauMas Apartment Complaint Management System with Email Notification, to design a web-based complaint management system with email notification for DanauMas Apartment using the data gathered, to implement and develop DanauMas Apartment Complaint Management System with Email Notification. The methodology used in order to complete this project is Waterfall model which consist of requirement gathering and analysis phase, design phase and implementation phase. Based on the findings, 14 use cases are created with 2 actors for the system. Each of the phase have their deliverables that are finished, the problems are being solved as well as objective are achieved.